2013
DOI: 10.1128/mcb.00980-12
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 Controls the Subcellular Localization of the Rho Guanine Nucleotide Exchange Factor Net1A To Regulate Focal Adhesion Formation and Cell Spreading

Abstract: RhoA is overexpressed in human cancer and contributes to aberrant cell motility and metastatic progression; however, regulatory mechanisms controlling RhoA activity in cancer are poorly understood. Neuroepithelial transforming gene 1 (Net1) is a RhoA guanine nucleotide exchange factor that is overexpressed in human cancer. It encodes two isoforms, Net1 and Net1A, which cycle between the nucleus and plasma membrane. Net1 proteins must leave the nucleus to activate RhoA, but mechanisms controlling the extranucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 48 publications
8
51
1
Order By: Relevance
“…Notably, mutation of both NLS sequences together caused a significant relocalization of Net1A outside the nucleus that was as strong as that caused by coexpression of constitutively active V 12 Rac1, which potently stimulates Net1A localization to the cytosol and plasma membrane (Fig. 1E,F) (Carr et al, 2013a). Taken together, these data indicate that Net1 isoforms contain additional, unrecognized NLS sequences that contribute significantly to their nuclear localization.…”
Section: Identification Of Nls Sequences Within Net1 and Net1asupporting
confidence: 59%
See 4 more Smart Citations
“…Notably, mutation of both NLS sequences together caused a significant relocalization of Net1A outside the nucleus that was as strong as that caused by coexpression of constitutively active V 12 Rac1, which potently stimulates Net1A localization to the cytosol and plasma membrane (Fig. 1E,F) (Carr et al, 2013a). Taken together, these data indicate that Net1 isoforms contain additional, unrecognized NLS sequences that contribute significantly to their nuclear localization.…”
Section: Identification Of Nls Sequences Within Net1 and Net1asupporting
confidence: 59%
“…Recently we have shown that activation of Rac1 downstream of integrin ligation causes a robust, temporally regulated relocalization of the Net1A isoform to the plasma membrane. Moreover, Net1A relocalization is required for focal adhesion maturation and cell spreading in breast cancer cells (Carr et al, 2013a). However, the mechanism by which Rac1 stimulates Net1A relocalization is not known.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations